Transcranial direct current stimulation influences repetitive bimanual force control and interlimb force coordination - Lee, Joon Ho; Kang, Nyeonju (Experimental brain research, 2023)
This study aimed to investigate the potential effect of bilateral transcranial direct current stimulation (tDCS) on repetitive bimanual force control and force coordination in healthy young adults. In this sham-controlled crossover study, 18 right-handed young adults were enrolled. Repetitive bimanual handgrip force control trials were performed by the participants at 40% of maximum voluntary contraction until task failure. We randomly provided bilateral active and sham tDCS to the primary motor cortex (M1) of each participant before conducting the repetitive bimanual force control task. We quantified the number of successful trials to assess the ability to maintain bimanual force control across multiple trials. Moreover, we estimated bimanual force control and force coordination by quantifying force accuracy, variability, regularity, and correlation coefficient in maximal and adjusted successful trials. Force asymmetry was calculated to examine potential changes in motor dependency on each hand during the task. Bilateral tDCS significantly increased the number of successful trials compared with sham tDCS. The adjusted successful trial revealed that participants who received bilateral tDCS maintained better bimanual force control and coordination, as indicated by decreased force variability and regularity as well as more negative correlation coefficient values in comparison with sham condition. Moreover, participants who received bilateral tDCS produced more force from the dominant hand than from the nondominant hand in both maximal and adjusted successful trials. These findings suggest that bilateral tDCS on M1 successfully maintains bimanual force control with better force coordination by modulating motor dependency.